2004
DOI: 10.1007/bf02351000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of auditory evoked potential parameters in the presence of radiofrequency fields using a support vector machines method

Abstract: The paper presents a study of global system for mobile (GSM) phone radiofrequency effects on human cerebral activity. The work was based on the study of auditory evoked potentials (AEPs) recorded from healthy humans and epileptic patients. The protocol allowed the comparison of AEPs recorded with or without exposure to electrical fields. Ten variables measured from AEPs were employed in the design of a supervised support vector machines classifier. The classification performance measured the classifier's abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 15 publications
(6 reference statements)
4
25
2
Order By: Relevance
“…This augmented N1 effect is inconsistent with the reduced N1 (Hamblin et al, 2004;Maby et al, 2004) and the null effect (Kleinlogel et al, 2008;Hamblin et al, 2006) during 2G exposure that has been previously reported, and so it is difficult to 21 interpret. One possibility is that the difference may be due to the different age groups sampled.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This augmented N1 effect is inconsistent with the reduced N1 (Hamblin et al, 2004;Maby et al, 2004) and the null effect (Kleinlogel et al, 2008;Hamblin et al, 2006) during 2G exposure that has been previously reported, and so it is difficult to 21 interpret. One possibility is that the difference may be due to the different age groups sampled.…”
Section: Discussioncontrasting
confidence: 72%
“…For example, three studies reported MP-related changes in event-related spectral power, but these were in different directions and frequencies (increase in 18.75Hz to 31.25Hz, Eulitz et al, 1998;decrease in 1-4Hz and increase in 8-12Hz, Croft et al, 2002; changes in 4-8Hz and 15Hz, Krause et al, 2006). Similarly, although there was consistency in event-related potential (ERP) research in that reduced N1 amplitude and latency was found by both Hamblin et al (2004) and Maby et al (2004), Hamblin et al (2006) were not able to replicate those 3 results with a stronger research design that had the added benefit of double-blinding, and this lack of effect was replicated by Kleinlogel et al (2008). Further, a very recent study did not find any MP-effect on mismatch negativity (an ERP index of auditory preattentive change detection) (Kwon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Please note that (like in ABR testing) in our own experiments, unlike in works by other authors presented The authors have found that EMF exposure of 12 healthy volunteers resulted in a drop of N100 wave amplitude and latency, and an increase in P300 wave amplitude. Similar conclusions have been reported by Maby et al [16], who have demonstrated that EMF exposure results in lower amplitude and shorter latency of N100 wave. Both authors re-examined the question to verify their earlier results.…”
Section: Discussionsupporting
confidence: 92%
“…The EMF exposure was achieved by connecting the phone with the base station during the test. The tests were conducted at the same hours (15)(16)(17)(18) only during week days. The call was simulated by directly wiring the phone to a tape recorder playing a pre-recorded voice message, thus generating an acoustic wave which, after it had been converted to a digital form, was radiated as electromagnetic wave.…”
Section: Exposure To Emfmentioning
confidence: 99%
“…Moreover, it might be that the RF influence all AEPs recorded on the scalp surface and not on specific areas. Thus, other devices may be more pertinent, such as in other studies [Maby et al, , 2004 where the correlation was computed between AEPs recorded on the same electrode during two different phases. …”
Section: Discussionmentioning
confidence: 99%